Implementation of Problem-Based Learning in CAD Instruction for Automotive Engineering Students : Classroom Action Research on Engagement and Learning Outcomes - Zulfadli Zulfadli; Mohd Azaman Md Deros; Rahmadani Rahmadani; ilham Yuliady Ilham Yuliady (Universitas Negeri Padang, 2026)
Low student engagement and modest Computer-Aided Design (CAD) learning outcomes remain challenges in automotive engineering education. This study examined the implementation of Problem-Based Learning (PBL) to support student engagement and CAD learning achievement in an Automotive Engineering course. A Classroom Action Research design was conducted in two cycles comprising planning, action, observation, and reflection. The participants were 25 Automotive Engineering students in the 2025/2026 even semester. Data were collected through observation, pre-test, post-test, and documentation, and analyzed descriptively. The results showed that learning mastery increased from 72% in Cycle I to 88% in Cycle II, while the average score increased from 70.04 to 78.48. Classroom observations also indicated more active participation in discussion, problem-solving, group work, and presentations. These findings suggest that PBL can support CAD learning achievement and student engagement in this classroom action context.